Apparent digestibility coefficients of local palm kernel cakes, rice bran, maize bran and sago flour in the GIFT strain of Nile tilapia (Oreochromis niloticus). Issue 2 (3rd April 2022) - Yossa, Rodrigue; Ahmad Fatan, Nurulhuda; Fairchild, James; Schrama, Johan W.
ABSTRACT: An experiment was conducted to estimate the apparent digestibility coefficients (ADC) of macronutrients and energy of local palm kernel cakes, rice bran, maize bran and sago flour in Nile tilapia, Oreochromis niloticus (average initial body weight of 30.49 ± 0.38 g). A reference (basal) diet was formulated to contain 33% crude protein, 7% crude fat and 390 Kcal/100 g diet, all on a dry matter basis. The acid-insoluble ash was used in all the diets as the digestibility marker. The experiment lasted 37 days, including a growth phase of 28 days followed by a feces collection phase of 9 days. The results showed that the ADCs of dry matter, crude protein, crude lipid, ash, crude fiber, total carbohydrate and gross energy were 79.74%, 83.53%, 78.79%, 83.84%, 75.53%, 78.20% and 79.25% for the conventional palm kernel cake, 46.36%, 34.59%, 47.89%, 34.94%, 60.35%, 51.69% and 47.96% for refined palm kernel cake, 58.67%, 51.00%, 65.10%, 60.39%, 63.59%, 59.44% and 60.50% for rice bran, 79.24%, 94.03%, 80.34%, 99.69%, 83.83%, 76.85% and 78.61% for maize bran, and 33.74%, negative value, negative value, negative value, 8.49%, 47.65% and 35.96% for sago flour in tilapia, respectively. The present study generated original information on the digestibility of nutrients contained in these local foodstuffs, which represents a baseline, original information that could be used to formulate least-cost local feeds. However, to account for the changes in the nutrient content of these local associated with seasonality, plant variety and improvement in ingredient processing on the quality of the ingredients available on local markets, it would be interesting to collect additional samples, several times a year and run similar digestibility experiments on a regular basis, in order to have a comprehensive database that could be used by local feed miller to manufacture feed for small fish farm holders.